2015
DOI: 10.1016/j.renene.2014.11.079
|View full text |Cite
|
Sign up to set email alerts
|

Tidal resource extraction in the Pentland Firth, UK: Potential impacts on flow regime and sediment transport in the Inner Sound of Stroma

Abstract: Large-scale extraction of power from tidal streams within the Pentland Firth is expected to be underway in the near future. The Inner Sound of Stroma in particular has attracted significant commercial interest. To understand potential environmental impacts of the installation of a tidal turbine array a case study based upon the Inner Sound is considered. A numerical computational fluid dynamics model, Fluidity, is used to conduct a series of depth-averaged simulations to investigate velocity and bed shear stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 46 publications
5
82
1
Order By: Relevance
“…A variety of methods have been used for the implementation of turbines in coastal array models: in two-dimensional models, the impact of turbines is often included as an additional component of bottom friction within the array footprint, either averaged over the whole array or as individual turbines [33,34,42]. The value used is often based on actuator disk theory with correction factors applied when array scale extraction is considered [43,44].…”
Section: Coastal Area Modellingmentioning
confidence: 99%
“…A variety of methods have been used for the implementation of turbines in coastal array models: in two-dimensional models, the impact of turbines is often included as an additional component of bottom friction within the array footprint, either averaged over the whole array or as individual turbines [33,34,42]. The value used is often based on actuator disk theory with correction factors applied when array scale extraction is considered [43,44].…”
Section: Coastal Area Modellingmentioning
confidence: 99%
“…The use of geophysical fluid dynamics simulations in the context of environmental impact assessment [2,3,4,5,17,26] and coastal infrastructure optimisation [31] is becoming common place. Robust mesh generation is therefore required, enabling an adequate representation of coastal infrastructure, within inherently complex geophysical domains.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the parameterisation of geo- metrically complex turbines has been common practice in studying the impact of tidal power generation arrays on sedimentation patterns [5]. However, recent studies have an increasingly detailed geometric description of the tidal turbines [33], as the focus shifts on tidal device per-formance, loading, survivability, interaction between devices, and tidal array optimisation in realistic domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study, Neill et al [7] found that tidal turbines could also impact sand bank formation and evolution near headlands. In the Pentland Firth, Martin-Short et al [8] used a high resolution hydrodynamic model to identify areas of sediment erosion and deposition, based on critical bed shear stress distributions calculated by the model. They found that installing arrays of more than 85 tidal turbines in the Inner Sound had the potential to significantly displace areas of sediment accumulation from the sides of the channel towards the centre, as the flow was diverted around the array.…”
Section: Introductionmentioning
confidence: 99%